Measurement and Experimental Testing of Models for the Estimation of HourlySolar Radiation on Vertical Surfaces at Mexico City - Y. Maldonado Sánchez, Liliana; Valdés Barrón, Mauro; Polo Martínez, Jesús; Martín Chivelet, Nuria (International Journal of Engineering and Technology, 2018)
This paper presents the results of measuring global solar irradiation in horizontal and vertical surfaces North, South, East and West with the aim to determine the energy loads in which buildings are subjected to in Mexico city, in order to provide the necessary information firstly, for planning and design of new buildings and secondly, for cost benefit analysis in the adaptation of already built structures. Solar irradiation on vertical surfaces plays a major role to determine thermal and energy performance of a building especially important for analysis of active and passive solar systems. A full year data of measurements (2014) have been compiled and analyzed. In addition, the hourly data of this horizontal and vertical measurements were compared with hourly radiation data calculated by means of two different models: the isotropic sky model (Hottel and Woertz model) and one anisotropic sky model (Perez model).  The performance of the models were assessed by two common statistical parameters: the relative root mean square error (RMSE) and the mean bias error (MBE). Perez model presented better performance through the year in north, east and west façades, and the isotropic model in south façade.